EVALUATION OF THE EFFECTS OF CORPORATE ENTREPRENEURSHIP - Erić Nielsen, Jelena; Stojanović-Aleksić, Vesna; Bošković, Aleksandra (Poslovna ekonomija, 2017)
In order for corporate entrepreneurship to be encouraged and developed, it is necessary to continuously monitor and evaluate activities in this area. It is particularly important to measure the level of innovation, changes in the competitive position, internal efficiency and impacts on performance. Starting from this point of view, this paper aims to acquire knowledge about the most important instruments for the evaluation of entrepreneurial activities at the enterprise level, individual level, as well as evaluation of individual contributions to achieving organizational performance. We identified the main instruments for measurement, which are used at the organizational level, including: Entrepreneurial Intensity, Corporate Entrepreneurship Climate Instrument, Entrepreneurial Health Audit, Zahra’s 14-point scale and Entrepreneurial Management. Also, we analyzed the ways to evaluate the entrepreneurial activities at the level of individual entrepreneurial projects. The contribution of the paper is reflected in highlighting the importance of evaluation of the effects of corporate entrepreneurship, taking into account not only the organizational, but also individual performance, as well as providing insight into the most important instruments that are theoretically relevant and extremely useful in practice.
Keywords: Performances; instruments; evaluation; entrepreneurship; Corporate Entrepreneurship